2013
DOI: 10.1371/journal.pone.0075894
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of shRNA by AAV9 Provides Highly Efficient Knockdown of Ubiquitously Expressed GFP in Mouse Heart, but Not Liver

Abstract: AAV9 is a powerful gene delivery vehicle capable of providing long-term gene expression in a variety of cell types, particularly cardiomyocytes. The use of AAV-delivery for RNA interference is an intense area of research, but a comprehensive analysis of knockdown in cardiac and liver tissues after systemic delivery of AAV9 has yet to be reported. We sought to address this question by using AAV9 to deliver a short-hairpin RNA targeting the enhanced green fluorescent protein (GFP) in transgenic mice that constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…However, the knockdown efficiency (36% reduction of mRNA level) in the liver is much lower than that in the heart (68% reduction of mRNA level). This is consistent with the previous study showing that, despite higher viral genome presence in the liver, systemic delivery of shRNA by rAAV9 provides more efficient gene knockdown in the heart 35 . It is possible that hepatocytes are more proliferative than cardiomyocytes and are more actively undergoing cell division after rAAV9 administration at the neonatal ages, which results in substantial vector genome dilution in the liver tissue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the knockdown efficiency (36% reduction of mRNA level) in the liver is much lower than that in the heart (68% reduction of mRNA level). This is consistent with the previous study showing that, despite higher viral genome presence in the liver, systemic delivery of shRNA by rAAV9 provides more efficient gene knockdown in the heart 35 . It is possible that hepatocytes are more proliferative than cardiomyocytes and are more actively undergoing cell division after rAAV9 administration at the neonatal ages, which results in substantial vector genome dilution in the liver tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Although the U6 promoter is ubiquitously active in mouse tissues, a most striking inhibition of target mRNA (Trbp) by rAAV9.U6::shRNA was observed in the heart, but not in other organs (Figure 5). The liver is the most common organ transduced by different serotypes of rAAV 35,36 . However, the knockdown efficiency (36% reduction of mRNA level) in the liver is much lower than that in the heart (68% reduction of mRNA level).…”
Section: Discussionmentioning
confidence: 99%
“…We used AAV9 because it shows strong tropism for the heart, especially for cardiomyocytes, after a single tail vein injection 4, 24 . We found that cardiac STIM1 expression is reduced by 75% three weeks after administration of AAV9.sh Stim1 as compared to controls (Supplemental figure 1B-C).…”
Section: Resultsmentioning
confidence: 99%
“…13 We replaced the luciferase gene with the mouse GRP78 gene. 13 AAV9 vectors were purified, and their titers were determined as previously reported. 13 …”
Section: Aav9 Vector Constructionmentioning
confidence: 99%
“…13 All bioluminescence imaging was performed with the IVIS 100 system (Caliper Life Sciences, Hopkinton, MA).…”
Section: Bioluminescence Imagingmentioning
confidence: 99%